Evaluation of IT Service Level Infrastructure In Organizations Using ITIL (Information Technology Infrastructure Library) Version 3 Standardization - Achmad Randhy Hans; Gerry Firmansyah; Budi Tjahyono; Agung Mulyo Widodo (Asian Journal of Social and Humanities, 2024)
The rapid development of business and advancements in information technology today are highly significant, especially in supporting the progress of ongoing businesses. Many businesses, particularly startups, make information technology the backbone supporting every main business process to achieve their business goals. Startups that operate 24/7 require sufficiently robust information technology, which must always be ready to provide the needed services to support the business. IT service assessment is an activity commonly carried out within an organization to eval_uate the level of information system services it possesses. An assessment, particularly an IT service assessment, can be conducted independently if the organization has adequate tools and is equipped with the correct standards. The eval_uation of information system services can be carried out using various standards, such as ITIL. In this research, the researcher will conduct an assessment using ITIL standards in the form of a website, which can serve as a tool. This website assessment application focuses on the domains of Service Management and Service Delivery, with the expectation that the services provided by PT Loyal.id will improve further.